2021
DOI: 10.1177/25151355211057479
|View full text |Cite
|
Sign up to set email alerts
|

Safety and reactogenicity of the adjuvanted recombinant zoster vaccine: experience from clinical trials and post-marketing surveillance

Abstract: An adjuvanted recombinant zoster vaccine (RZV) is licensed for the prevention of herpes zoster. This paper reviews its safety and reactogenicity. A pooled analysis of two pivotal randomized Phase-3 trials (NCT01165177, NCT01165229) in adults ⩾50 years found that more solicited adverse events (AEs) were reported with RZV than placebo. Injection site pain was the most common solicited AE (RZV: 78.0% participants; placebo: 10.9%). Grade-3 pain occurred in 6.4% of RZV and 0.3% of placebo recipients. Myalgia, fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Considering that aged individuals are main target population of zoster vaccine and these cohorts are more susceptible to cardiovascular diseases, the inappropriate platelet activation induced by Shingrix may pose a potential risk. Besides, the increased expression of pain-related genes also supported the clinical findings that local injection site pain is the most common solicited adverse event in Shingrix recipients [36]. In addition, it should be noted that our mRNA vaccine encodes full-length gE, which is in contrast with Shingrix that contains truncated form of gE (1-544 aa) [55].…”
Section: It Has Been Reported That Host Immune Responses To Vzv Infec...supporting
confidence: 77%
See 1 more Smart Citation
“…Considering that aged individuals are main target population of zoster vaccine and these cohorts are more susceptible to cardiovascular diseases, the inappropriate platelet activation induced by Shingrix may pose a potential risk. Besides, the increased expression of pain-related genes also supported the clinical findings that local injection site pain is the most common solicited adverse event in Shingrix recipients [36]. In addition, it should be noted that our mRNA vaccine encodes full-length gE, which is in contrast with Shingrix that contains truncated form of gE (1-544 aa) [55].…”
Section: It Has Been Reported That Host Immune Responses To Vzv Infec...supporting
confidence: 77%
“…A promising vaccine candidate should possess a high safety profile. Despite the fact that Shingrix is highly effective to prevent zoster, clinical trials and post-marketing surveillance have reported a high local and systemic reactogenicity of Shingrix [36]. In this study, we preliminarily evaluated safety properties of ZOSAL by monitoring levels of various serum biochemical parameters following vaccination, including liver and kidney enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that aged individuals are the main target population of the zoster vaccine and these cohorts are more susceptible to cardiovascular diseases, the inappropriate platelet activation induced by Shingrix may pose a potential risk. Besides, the increased expression of pain-related genes also supported the clinical findings that local injection site pain is the most common solicited adverse event in Shingrix recipients [ 36 ]. In addition, it should be noted that our mRNA vaccine encodes full-length gE, which is in contrast with Shingrix that contains a truncated form of gE (1-544 aa) [ 55 ].…”
Section: Discussionsupporting
confidence: 55%
“…A promising vaccine candidate should possess a high safety profile. Despite the fact that Shingrix is highly effective in preventing zoster, clinical trials, and post-marketing surveillance have reported a high local and systemic reactogenicity of Shingrix [ 36 ]. In this study, we preliminarily evaluated the safety properties of ZOSAL by monitoring levels of various serum biochemical parameters following vaccination, including liver and kidney enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the difficulty of operation and the similarity in the pattern of early adverse events between the present study and the existing literature, this monitoring approach should be maintained due to the significant time lag associated with the methods described later, especially in the event of unexpected AESI occurrences. 17 18 19 20 21 22 23 24 25 26 27 Second, retrospective screening was not efficient based on the scale of efforts, and the number of participants included in this study was too small to observe rare AESI cases. Moreover, the rate of AESI may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%